2017
DOI: 10.1111/bju.14049
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre evaluation of magnetic resonance imaging supported transperineal prostate biopsy in biopsy‐naïve men with suspicion of prostate cancer

Abstract: MRI-based transperineal biopsy performed at high-volume tertiary care centres with a significant experience of prostate mpMRI and image-guided targeted biopsies yielded high detection rates of Gleason score 7-10 cancer. Prostate biopsies may not be needed for men with low PSAD and an unsuspicious MRI. In patients with high probability lesions, combined targeted and systematic biopsies are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
126
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(151 citation statements)
references
References 34 publications
7
126
4
Order By: Relevance
“…From all the reports and published literature to date the TVT would appear to be as, if not more, effective than all other procedures without having a higher complication rate. The data in the present paper by Braga et al [1] should reassure healthcare providers that TVT continues to be a safe and effective surgical strategy for the management of SUI in women.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…From all the reports and published literature to date the TVT would appear to be as, if not more, effective than all other procedures without having a higher complication rate. The data in the present paper by Braga et al [1] should reassure healthcare providers that TVT continues to be a safe and effective surgical strategy for the management of SUI in women.…”
mentioning
confidence: 56%
“…undertaken. In the present study from Italy and Switzerland, however, Braga et al have managed to follow up 46 out of 52 (88.4%) women who had a traditional TVT inserted between 1998 and 2000 [1]. The remaining patients were lost to follow-up or had died in the intervening period.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…This is also supported by a multicentre study by Hansen et al. , which demonstrated that the NPV of a negative mpMRI for excluding Gleason 7–10 cancer was 80%, but improved to 91% with a PSA density of <0.1 ng/mL/mL, and to 89% with a PSA density of <0.15 ng/mL/mL. It is important to note that these studies used transperineal biopsies rather than 12‐core transrectal biopsies, suggesting the latter to be a more unreliable reference test with a greater probability of missing clinically significant cancer on systematic sampling.…”
mentioning
confidence: 69%
“…It was agreed but not in consensus that biopsy options in equivocal mpMRI should include MR‐guided biopsy (visually estimated, image fusion or in‐bore; eight of 12 panelists), transperineal systematic biopsy (seven of 12 panelists) or combined targeted and systematic sampling (seven of 12 panelists) of the gland. Emerging evidence shows no statistical difference between the use of combined targeted and systematic biopsy vs each biopsy technique alone for significant cancer detection in equivocal lesions .…”
Section: Resultsmentioning
confidence: 99%